A silent opponent: Staphylococcus aureus and its impact on wrestlers - Thomas, Talia; Moore, Angela; Nath, Swapan; Kearns, Greg (International Journal of Sports Medicine, 2025)
Community acquired methicillin resistant Staphylococcus aureus infections have surged dramatically over the past decade. Athletes in contact sports, especially wrestlers, represent a unique subset of young, healthy individuals who are at heightened risk for transmitting methicillin resistant Staphylococcus aureus. The sport of wrestling has seen a significant increase in participation, particularly among adolescents, underscoring its growing popularity and the urgent need to address this issue. Unfortunately, the rates of community acquired methicillin resistant Staphylococcus aureus have followed a similar upward trend. Treatment options for community acquired methicillin resistant Staphylococcus aureus vary, ranging from topical or systemic antibiotics to more invasive interventions like incision, drainage, and intralesional injections. Preventive measures are also essential and include avoiding shared equipment, meticulous mat and gear cleaning, and eliminating bacterial colonization. While existing research supports the effectiveness of decolonization strategies in hospital settings, there is a pressing need to adapt and implement these approaches within the wrestling community. Current prevention methods, such as mat cleaning and skin checks before competitions, are insufficient on their own. By adopting more comprehensive decolonization protocols tailored to the wrestling environment, we can better protect athletes and reduce the incidence of community acquired methicillin resistant Staphylococcus aureus skin infections.
Keywords: transmission; carriage; prevention; athletes; infection